Penerjemahan Majas Hiperbola dalam Novel Kazemachi No Hito Karya Ibuki Yuki - Sri Wahyuni, Luh Made; Indra Pradhana, Ngurah (Humanis, 2017)
The title of this research is “Hyperbole Translation in The Novel Entitled Kazemachi No Hito by Ibuki Yuki”. The method of this research is descriptive qualitative. The source of data is a novel entitled Kazemachi No Hito and its translation. This research aims to analyze the categories of hyperbole and hyperbole translation strategies used by the translator in translating hyperbole. The theory for analyzing the categorization of hyperbole is based on Sato’s theory (1978) and translation strategies by Larson (1984). The result of analysis shows that there are 80 data of hyperbole found in the novel Kazemachi No Hito. The data are categorized in five categories, there are 52 data of figurative hyperbole, 16 data expression of lies hyperbole, 14 data of hyperbole that refers to feelings, 9 data of hyperbole that refers to body, and 9 data logical expression hyperbole. There are five translation strategies found in this research. The result shows that only figurative hyperbole can be translated into simile.